The nature of Late Cenozoic volcanism in the Udokan Range, northwestern segment of the Baikal Rift zone - Grachev A.F. (Федеральное государственное бюджетное учреждение науки Геофизический центр Российской академии наук, 2017)
Newly obtained major-component, trace-element, and rare-earth element (REE) analyses are used to gain insight into the nature of Late Cenozoic volcanism in the Udokan Range. The composition of the lavas is analyzed in each lava flow and it is demonstrated that the rocks define a bimodal differentiated series with a Daly gap. The absence of andesite is seen not only in the summarizing diagrams but also in individual vertical sections of the volcanic rocks. The petrochemical specifics of volcanics in the Udokan Range involves broad variations in the TiO$_2$ concentrations: from 0.22 to 4.41 wt %. The REE patterns of the volcanics show a trend analogous to that of oceanic islands basalts (OIB). The compositional specifics of the rocks suggest that the basalt-trachyte series was derived from a single mantle source related to a mantle plume.
Keywords: VOLCANISM; DALY GAP; MANTLE PLUME; BAIKAL RIFT; UDOKAN RANGE